Quantitative and qualitative condylar changes following stabilization splint therapy in patients with temporomandibular joint disorders with and without skeletal lateral mandibular asymmetry: a cone beam computed tomographic study - Mazen Musa; Riham Awad; Salma Izeldin; Yunshan Zhao; Hao Wu; Lu Wang; Saba Ahmed Al-hadad; Bdr Sultan Saif; Madiha Mohammed Saleh Ahmed; Xi Chen (BMC, 2024)
Abstract Background Temporomandibular disorders (TMDs) encompass pain and dysfunction in the jaw, muscles, and adjacent structures. This study aimed to explore the quantitative (condylar position, morphology) and qualitative (bone mineral density (BMD)) therapeutic outcomes following a stabilization splint (S.S.) therapy in adult patients diagnosed with TMD (Arthralgia) with/without lateral mandibular asymmetry (MA) using cone beam computed tomography (CBCT). Methods In this retrospective clinical study, 60 adult TMD patients who received S.S. therapy were enrolled and allocated into the TMD group (TMDG) and TMD with MA group (TMD + MAG). The diagnosis was made according to the Diagnostic Criteria for TMD (DC/TMD) AXIS I. MA was measured from the mid-sagittal plane to the Menton point. CBCT was used to scan the temporomandibular joints pre- (T0) and post- (T1)-treatment for three-dimensional analysis. Intra- and intergroup statistical comparisons were performed using the Wilcoxon signed ranks and the Kruskal‒Wallis test. Results For quantitative comparisons, there was a statistically significant difference between T0 and T1 in the joint spaces of TMD + MAG (anterior, superior, posterior, and coronal lateral on the deviated side as well as in the superior, coronal medial joint space of the contralateral side). Morphologically, the deviated side had a narrower condylar width, reduced condylar height, and a steeper eminence angle. In contrast, the contralateral side tended to have a greater condylar length. For qualitative measurements, BMD also showed statistical significance between T0 and T1 in the majority of the condyle slopes (AS, SS, PS, and LS on the deviated side and in AS and MS on the contralateral side) of TMD + MAG. Additionally, only the AS and PS showed significance in TMDG. Conclusion Multiple joint space widening (AJS and CMS) and narrowing (SJS, PJS, and CLS) could characterize the deviated side in TMD + MA. Factors like narrower condylar width, reduced condylar height, and steeper eminence angle on the deviated side can worsen TMD + MA. Proper alignment of the condyle-disc position is essential for optimal function and load distribution, potentially affecting bone mineral density (BMD). MA plays a prominent role in disturbing bone densities. S.S. therapy shows more evident outcomes in TMD + MAG (on the deviated side compared to the contralateral side) than the TMDG.